Efeitos da temperatura e da turbidez no crescimento de Egeria densa Planch - Machado, Raphael (2020)
Mathematical modeling of macrophyte growth is a predictive tool that can be useful, for example, for planning plant population management strategies. In this study, a kinetic model was used to evaluate the growth of submerged aquatic macrophyte Egeria densa under laboratory conditions that simulated temperature and turbidity conditions. Thus, the growth of E. densa was evaluated under two temperatures (25 and 27 °C) and different conditions of turbidity (0%, 18.5%, 37% and 55.5%),with four types of soil:(i) Gleissolo Haplic Eutrophic, (ii) Dystrophic Red Latosol, (iii) Red Latosol Dystrophic and (iv) Quartzarenic Neosols. The experiments were conducted for 60 days. The plants were cultivated under controlled conditions (12-hour photoperiod, radiation intensity of 4.31x10-3μmol mon-1 cm-2) in borosilicate containers in germination chambers. Bioassays were randomly allocated to maintain uniform radiation. To determine the growth of the individuals of Egeria densa, the size of the plants was evaluated, and every four days, electrical conductivity, pH, and turbidity were measured. The temporal variation of the accumulated lengths of E. densa was fitted to a logistic model to estimate the duplication time and Q10 were estimated. In general, it was found that the increase in temperature (p < 0.05) for the different types of soils contributed significantly to the increase in accumulated growth, biomass increase, and on the number of branches and roots of E. densa. Turbidity was related to a shorter accumulated length, except for dystrophic Red Latosol, in which the augment in turbidity caused an increase to the accumulated length. As for the composition of the soils, it was found that nitrogen tended to decrease accumulated growth and potassium contributed to the increase in growth, while phosphorus (p-value> 0.05) was not statistically significant. It was concluded that the temperature increases at 2°C was the predominant factor that contributed most to creased growth of E. densa, potentiating its invasion and proliferation in aquatic environments.